Development of Electronic Students’ Worksheet Based on Problem Based Learning on Air Pollution Sub Matter - Salsabilla, Fitri Wahyuni; Destiansari, Elvira; Meilinda (Universitas Negeri Jakarta, 2024)
This research is development research with the aim to produce teaching material products in the form of PBL-based electronic student worksheets on air pollution sub-materials that will be used during the learning process, so that students can be more active and independent. This type of research is development research using the ADDIE model (analysis, design, development, implementation, evaluation), but this research is limited to the development stage. This research was conducted at State Senior High Schools in Palembang in the 2023/2024 school year. The sample in this study was class X students totaling 12 people. Sampling in this study using purposive sampling technique. electronic student worksheets are designed using the Canva and liveworksheets applications; after completing the design of electronic student worksheets, they are assessed by material and media validators using an instrument in the form of a validation questionnaire. After the electronic student worksheet is declared valid, the electronic student worksheet is applied to students in a small group trial. Based on the validation results with the Kappa calculation, the electronic student worksheets were declared valid with a Kappa value of 1. Electronic student worksheets also fall into the very practical category based on the teacher's practicality questionnaire which obtained a percentage of 100%, while the students' practicality questionnaire obtained an average percentage of 90.68%. Based on the results of the validation and practicality questionnaires of teachers and students, it can be concluded that PBL-based electronic student worksheets are valid and feasible to use during the learning process on air pollution sub-materials.